Impact of United States Food and Drug Administration's boxed warnings on adverse drug reactions reporting rates and risk mitigation for multiple myeloma drugs. (May 2013) - Garg, Vishvas; Raisch, Dennis W; McKoy, June M; Trifilio, Steven M; Holbrook, Jamiee; Edwards, Beatrice J; Belknap, Steven M; Samaras, Athena T; Nardone, Beatrice; West, Dennis P
<x xml:space="preserve">Abstract</x> Purpose: To determine the relationship between boxed warnings issuance by the US Food and Drug Administration (FDA) and the proportional reporting rates of the associated adverse drug reactions (ADRs) to the FDA's Adverse Event Reporting System (FAERS) for multiple myeloma (MM) drugs. Methods: We compiled a list of all FDA approved MM drugs and identified their associated ADR boxed warnings, through FDA's website and physician desk reference. Drugs that were issued boxed warnings after their market launch were included in the analysis, i.e., melphalan, thalidomide, vincristine, carmustine and doxorubicin. For each drug/ADR boxed warning combination, we retrieved all reported cases from the FAERS and calculated their Empiric Bayes Geometric Means (EBGMs), in pre- and post-boxed warning periods. Chi-square tests were performed to compare serious adverse drug events before and after boxed warnings for all drug/ADR combinations. Results: A total of 10 drug/ADR boxed warning combinations were identified, of which EBGM signals increased for six combinations after a boxed warning was issued. Reports of serious adverse drug events also increased significantly (p < 0.05). Conclusion: Boxed warnings were associated with increased FAERS reporting, indicating increased awareness of ADRs for MM drugs. Proactive pharmacovigilance programs, such as the FDA's Mini-Sentinel Project, may improve timeliness of detection of rare ADRs.